Fatores organizacionais no processo ético disciplinar sobre o erro no trabalhode enfermagem - Andrade, Flávia Pontes Guerra de Santana (2018)
Objective: To analyze the organizational factors contemplated in the Disciplinary Ethical Process (DEP) on the error in nursing work in light of the Swiss Cheese model by James Reason and the London Protocol. Methods: This master dissertation had two articles as a product. The first refers to a meta-synthesis made in the database of the BVS with the descriptors "erro and enfermagem", in the period from 2012 to 2017, in national and international literature, using thematic content analysis. The second article deals with a unique case study of a DEP of the Regional Council of Nursing of Bahia, with delineation of documentary research and qualitative approach. For the analysis of the organizational factors contained in the DEP, the London Protocol and the Theory of James Reason, 2000 to 2014, were used. Results: In the meta-synthesis 10 publications were analyzed, the following categories being identified and described, according to the theory of the Swiss Cheese model: Concept and Types of Error, Error Approach, Defense Barriers, Active Failures and Latent Conditions. Only two publications addressed the theory in depth. In the second article it was possible to identify the organizational factors contained in the DEP that contributed to the nursing error. Such as financial restrictions; organizational structure; policies, patterns, ambiguous protocols, unclear rules; and safety culture and priorities, according to the London Protocol and the James Reason Theory. Conclusions: Analyzing a Disciplinary Ethical Nursing Process in light of the Swiss Cheese Model by James Reason and the London Protocol made it possible to demonstrate the organizational factors that contributed to the error in nursing work. The studies presented in this paper on the subject reveal the dimension of the problem and the paramount need in the development of strategies for detection, research and intervention against the errors that occur in health services, with the aim of reducing and minimizing the risks for error. Understanding error as inherent to the human condition and facing the possibility of avoiding it allows us to recognize it as part of a system failure